1988
DOI: 10.1007/bf01550977
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of oxygen free radicals in ethanol-induced gastric mucosal damage in rats

Abstract: The involvement of oxygen free radicals in the development of the ethanol-induced gastric mucosal damage has been investigated. We found that oral administration of superoxide dismutase reduced the incidence of ethanol-induced mucosal lesions. Reduction of superoxide dismutase activity by diethyldithiocarbamate led to a pronounced aggravation of mucosal damage. Inhibition of the chloride-bicarbonate channel by a stilbene derivative also aggravated the ethanol-induced hemorrhagic lesions. Neither glutathione pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(78 citation statements)
references
References 20 publications
1
76
0
1
Order By: Relevance
“…4) It has been suggested that production of oxygen free radicals plays a crucial role in the development of ethanol-induced gastric lesions. [5][6][7][8] The present study investigated the in vivo protective effect of astaxanthin isolated from the Xanthophyllomyces dendrorhous mutant against ethanol-induced gastric mucosal injury in rats. Peroxidation of lipids and changes in the activities of healing-related enzymes such as superoxide dismutase, catalase, and glutathione peroxidase were also monitored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) It has been suggested that production of oxygen free radicals plays a crucial role in the development of ethanol-induced gastric lesions. [5][6][7][8] The present study investigated the in vivo protective effect of astaxanthin isolated from the Xanthophyllomyces dendrorhous mutant against ethanol-induced gastric mucosal injury in rats. Peroxidation of lipids and changes in the activities of healing-related enzymes such as superoxide dismutase, catalase, and glutathione peroxidase were also monitored.…”
Section: Discussionmentioning
confidence: 99%
“…4) It has been suggested that ethanol-induced gastric damage is mediated by the generation of free radicals. [5][6][7][8] Recently, astaxanthin (3,3 0 -dihydroxy-, 0 -carotene-4,4 0 -dione) has been documented to provide important metabolic functions in animals, including conversion to vitamin A, 9) enhancement of immune response, 10,11) and protection against diseases such as cancer by scavenging oxygen radicals. [12][13][14][15][16] The antioxidant activity of astaxanthin has been reported to be approximately 10 times stronger than that of other carotenoids tested, including zeaxanthin, lutein, canthaxanthin, and -carotene, and 100 times greater than that of -tocopherol.…”
Section: Suppressive Effect Of Astaxanthin Isolated From the Xanthophmentioning
confidence: 99%
“…T here is growing evidence that lipid peroxidation (LP) could play a significant role in the pathogenesis of ethanol-induced gastric mucosal lesions, especially because oxygen radicals have been directly implicated in the damage of cell membranes after administration of that agent (Kvietys et al, 1990;Szelenyi and Brune, 1988;Terano et al, 1989). Indeed, the hypothesis that superoxide free radicals are involved in the immediate deleterious effect of ethanol on gastric mucosa seems to be confirmed by these studies.…”
mentioning
confidence: 94%
“…15 The antioxidant properties of Azadirachta indica together with some other factors yet to be established. Chattopadhyay in a similar work revealed that membrane damage by hydroxyl radical as measured by lipid peroxidation in stress ulcer is significantly blocked by neem extract.…”
Section: Discussionmentioning
confidence: 99%